Low Insulin-like Growth Factor-1 Influences Fatigue and Quality of Life in Children With Inflammatory Bowel Disease. Issue 5 (November 2018) - Lucia Casadonte, Chantal J.; Brown, Jeffrey; Strople, Jennifer; Neighbors, Katie; Fei, Lin; Alonso, Estella M.
ABSTRACT: Objective: Fatigue is common among patients with inflammatory bowel disease (IBD). Proinflammatory cytokines are elevated in chronic inflammation and can induce "sickness behaviors, " such as fatigue. Chronic inflammatory states also lead to growth hormone resistance, demonstrated by low levels of insulin-like growth factor (IGF-1) and elevated growth hormone. This study evaluated the relationship between IGF-1, proinflammatory cytokine levels, and fatigue in patients with IBD. Methods: In this prospective study children with IBD, ages 10 to 16 years, were recruited from a subspecialty ambulatory clinic. Participants and their parents completed age-appropriate generic and disease-specific health-related quality of life (HRQOL) instruments. Serum samples obtained at the same encounter were analyzed for Th17 cytokine and IGF-1 levels. HRQOL scores were compared to a healthy sample and HRQOL scores and cytokine levels were compared by IGF-1 z score quartiles. Results: A total of 67 patients with IBD were recruited, median age of 13.7 years (interquartile range, 11.7–15.3). Forty-eight (72%) had inactive disease based on Physician Global Assessment. Patients with IBD reported lower generic HRQOL ( P = 0.0006) and more fatigue ( P = 0.0004) than a healthy sample. Patients with IGF-1 z scores in the lowest quartile had significantly lower disease-specific HRQOL ( P = 0.01) and more fatigue ( P = 0.02) than the remainder of the cohort. Serum interleukin (IL)-10, IL-17A, IL-6, and interferon-γ were significantly higher in patients with IBD with IGF-1 z scores in the lowest quartile ( P < 0.05). Conclusions: Children with subclinical IBD experience more fatigue and lower generic HRQOL than healthy children. Lower IGF-1 z scores are associated with more fatigue, and this relationship may be mediated through proinflammatory cytokines. Abstract : Supplemental Digital Content is available in the text